Optimalisasi pengelolaan limbah minyak jelantah melalui pelatihan pembuatan lilin aromaterapi untuk mendukung ekonomi kreatif - Metatia Intan Mauliana; Nuril Lutvi Azizah (Penamas: Journal of Community Service, 2026)
Household used cooking oil waste represents one of the most abundant waste sources generated at the household level. Despite its economic potential when properly utilized, the management of this waste remains suboptimal. This community service activity aims to enhance the literacy, skills, and capacity of the Ikwam Group at SD Kreatif Muhammadiyah 2 Tulangan in processing used cooking oil waste into valuable products. The implementation methods include socialization on the impacts and utilization potential of used cooking oil, as well as training on simple purification processes and product creation, such as aromatherapy candles made from used cooking oil. Activity evaluation was conducted using participant response questionnaires based on the Likert scale. The results indicate that the program positively impacted participants' knowledge, motivation, skills, and awareness in household waste management. Based on the evaluation, the program achieved an 88.5% success rate, with an overall average score of 4.43, categorized as excellent. This initiative not only boosts partners' capacity for sustainable waste management but also opens opportunities for household-based creative economic development through the utilization of used cooking oil.